Creating a Model to Predict Time Intervals From Induction of Labor to Induction of Anesthesia and Delivery to Coordinate Workload. Issue 4 (December 2021) - Warner, L.L.; Hunter Guevara, L.R.; Barrett, B.J.; Arendt, K.W.; Peterson, A.A.; Sviggum, H.P.; Duncan, C.M.; Thompson, A.C.; Hanson, A.C.; Schulte, P.J.; Martin, D.P.; Sharpe, E.E.
Abstract : ( Int J Obstet Anesth . 2021;45:115–123) Recent evidence and guidelines supports offering induction of labor (IOL) to low-risk nulliparous women at 39 weeks' gestation to reduce risk of cesarean delivery (CD) or adverse neonatal outcomes. Surgical patient outcomes can be impacted by timing of surgery and this may translate to risk of maternal and neonatal outcomes depending on timing of delivery and care team staffing levels and availability. This study aimed to create a model to predict timing from IOL to request for anesthesia and subsequent delivery in order to optimize anesthesia and obstetric team workload during the most well-staffed hours.